1994
DOI: 10.1083/jcb.126.3.801
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lysophosphatidate- and thrombin-induced neurite retraction and neuronal cell rounding by ADP ribosylation of the small GTP-binding protein Rho.

Abstract: Abstract. Addition of the bioactive phospholipid lysophosphatidic acid (LPA) or a thrombin receptor-activating peptide (TRP) to serum-starved N1E-115 or NG108-15 neuronal cells causes rapid growth cone collapse, neurite retraction, and transient rounding of the cell body. These shape changes appear to be driven by receptor-mediated contraction of the cortical actomyosin system independent of classic second messengers. Treatment of the cells with Clostridium botulinum C3 exoenzyme, which ADP-ribosylates and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
409
3
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 586 publications
(439 citation statements)
references
References 69 publications
24
409
3
1
Order By: Relevance
“…In contrast, the R cell population reached a peak at 15-30 min and then gradually decreased ( Figure 2, d and f). The increase in the R cell population at 15 min was significantly inhibited by pretreatment with CD (Figure 3c), consistent with previous results showing that process retraction and cell rounding require actin polymerization (Jalink et al, 1994). These results indicated that LPA induced rapid actin depolymerization that was associated with loss of membrane ruffling, which was followed by actin polymerization that induced process retraction and cell rounding.…”
Section: Effects Of Lpa On Cell Shape and Actin Cytoskeletonsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, the R cell population reached a peak at 15-30 min and then gradually decreased ( Figure 2, d and f). The increase in the R cell population at 15 min was significantly inhibited by pretreatment with CD (Figure 3c), consistent with previous results showing that process retraction and cell rounding require actin polymerization (Jalink et al, 1994). These results indicated that LPA induced rapid actin depolymerization that was associated with loss of membrane ruffling, which was followed by actin polymerization that induced process retraction and cell rounding.…”
Section: Effects Of Lpa On Cell Shape and Actin Cytoskeletonsupporting
confidence: 80%
“…LPA-induced actin polymerization results in process retraction and cell rounding in neuronal cells such as N1E-115, or stress fiber formation in fibroblast cells (Ridley and Hall, 1992;Jalink et al, 1993). These cellular responses are mediated by actomyosin interactions through activation of the Rho pathway, produc- ing contractile forces that induce cell shape changes (Jalink et al, 1994;Tigyi et al, 1996;Kozma et al, 1997;Hirose et al, 1998;Kranenburg et al, 1999;Fukushima et al, 2000;Weiner et al, 2001). Herein, we have also shown that Rho is activated by LPA in TR cells and LPA-induced process retraction is blocked by a ROCK inhibitor or CD, which indicates the possible involvement of Rho and actomyosin for process retraction in TR cells (Figure 10).…”
Section: Lpa Induces Both Actin Depolymerization and Polymerization Wmentioning
confidence: 64%
“…Our data show that the engagement of VE-cadherin and subsequent activation of the Rho-ROCKtension pathway are responsible for this effect in endothelial cells and support prior associations of RhoA activity with inhibition of cell spreading (Jalink et al, 1994;Hirose et al, 1998;van Leeuwen et al, 1999). Importantly, signaling through the Rho pathway also mediates the VE-cadherinstimulated increase in FAs when changes in cell spreading are prevented.…”
Section: Discussionmentioning
confidence: 48%
“…A single mechanism that might account for these paradoxical effects involves increased intracellular tension. Rho-mediated intracellular tension has been shown to decrease cell spreading (Jalink et al, 1994;Hirose et al, 1998;van Leeuwen et al, 1999), an effect that is supported by theoretical models (Palecek et al, 1999). At the same time, Rho-mediated intracellular tension has also been shown to increase stress fiber formation, integrin density, and FA formation in many studies Ballestrem et al, 2001).…”
Section: Kda (mentioning
confidence: 60%
See 1 more Smart Citation